Gender, Diet, Health and Seasonality: A Study of Preschool Children in an Island Fishing Community - Datar, Francisco A. (Philippine Social Sciences Review; Social Sciences and Health Issue, Ed. Carmen C. Jimenez, 2010)
The field school in Behia offered an excellent opportunity to observe the effects of seasonality on the diet and health of preschool children in the community. The annual habagat season brings hunger and illness to the fishing community, with children the most usual victims. Males, in particular, are hit hardest, despite greater access to food, than females. This is discussed in terms of parental favoritism and the males, naturally weaker stress buffers.